A study on variability of quantitative sensory testing in healthy participants and painful temporomandibular disorder patients. (June 2014) - Yang, Guangju; Baad-Hansen, Lene; Wang, Kelun; Xie, Qiu-Fei; Svensson, Peter
Abstract Objectives: Quantitative sensory testing has mainly used thresholds to evaluate somatosensory sensitivity so far. The variability of different measures from session to session has also been investigated, but the variability of the single individual measures of a threshold or subject-based reports has not been considered. This study aimed to investigate the potential value of threshold variability in one session as a measure of internal consistency in somatosensory function. Methods: The standardized quantitative sensory testing battery developed by the German Research Network on Neuropathic Pain was performed bilaterally over the infraorbital, mental, and hand regions in 70 healthy and 22 temporomandibular disorder pain participants. Somatosensory variability was investigated by calculating the Coefficient of Variation of three to five repeated measures in one threshold determination. The influences of side, gender, site, age, and presence of pain on the somatosensory variability were evaluated. Results: In the healthy participants, somatosensory variability was region dependent: hand > mental and/or infraorbital for CDT, WDT, HPT, MDT-N, MPT-Y, MPT-N, WUR, and MPS (p ≤ 0.043), infraorbital > hand for VDT (p = 0.001), mental > infraorbital for HPT and WUR (p ≤ 0.001); and age dependent for WDT, TSL, CPT, HPT, MDT-Y, MDT-N, MPT-N, and WUR (p ≤ 0.017). Gender and side had no main effect on variability (p ≥ 0.136). The pain patients presented higher variability compared with healthy participants for TSL, MDT-N, MPT-Y, WUR, and PPT (p ≤ 0.033). Discussion: The somatosensory variability along with the threshold would be a more complete method to investigate the somatosensory disorders and underlying pain mechanisms. The correlation between pain duration and somatosensory variability should be studied further with different pain conditions.